1974
DOI: 10.1084/jem.140.1.126
|View full text |Cite
|
Sign up to set email alerts
|

Role of Complement in Induction of Antibody Production in Vivo

Abstract: There has been considerable recent progress in understanding of the mechanisms involved in cooperation between T and B lymphocytes in the induction of humoral antibody formation (see for example 1), but much still remains to be learned. The discovery of an interaction between lymphocytes and the fixed C3 component of complement (2-5), and the demonstration by Nussenzweig et al. that C3 receptors are a feature of B-cell populations (6-10), raise the possibility that C3 might play a part in this process (11). Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
111
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(118 citation statements)
references
References 43 publications
(47 reference statements)
7
111
0
Order By: Relevance
“…The first is the central role of complement in induction of immunological memory and normal humoral responses (reviewed in references 13,14). These effects have been ascribed to C3 (14).…”
Section: Resultsmentioning
confidence: 99%
“…The first is the central role of complement in induction of immunological memory and normal humoral responses (reviewed in references 13,14). These effects have been ascribed to C3 (14).…”
Section: Resultsmentioning
confidence: 99%
“…1A1-A5). Complement and CR are known to facilitate trapping of IC on FDC [11][12][13][14][15]; thus, IC strongly labeled FDC-reticula in both passively immunized WT and FccRIIB -/-mice. In contrast, neither anti-OVA Ab nor OVA in the presence of nonspecific rabbit serum (NSS) were retained on the FDC-reticula, confirming the importance of the IC.…”
Section: Fdc-mediated Ic Trappingmentioning
confidence: 99%
“…The ability to stimulate B cells depends in large measure on the ability of FDC to trap and present Ag to specific B cells. FDC capture and retain Ag in the form of IC, and starting in the early 1970s, a number of studies elegantly documented that complement and complement receptors (CR) were necessary for optimal IC trapping and retention [11][12][13][14][15]. Although, Fc receptors may not be as important as complement and CR in IC trapping, they do appear to enhance long-term retention of IC by FDC [3].…”
Section: Introductionmentioning
confidence: 99%
“…It was Mark Pepys who, in the 1970s, noted the influence of complement on the adaptive immune response [1]. He found that mice depleted of complement failed to develop potent antibody responses, although the effect was partially overcome by increasing the dose of injected antigen.…”
mentioning
confidence: 99%